Monocytes inhibit NK activity via TGF-β in patients with obstructive sleep apnoea. Issue 6 (15th June 2017) - Hernández-Jiménez, Enrique; Cubillos-Zapata, Carolina; Toledano, Victor; Pérez de Diego, Rebeca; Fernández-Navarro, Isabel; Casitas, Raquel; Carpio, Carlos; Casas-Martín, Jose; Valentín, Jaime; Varela-Serrano, Anibal; Avendaño-Ortiz, Jose; Alvarez, Enrique; et al.
Obstructive sleep apnoea (OSA) is associated with cancer incidence and mortality. The contribution of the immune system appears to be crucial; however, the potential role of monocytes and natural killer (NK) cells remains unclear. Quantitative reverse transcriptase PCR, flow cytometry and in vitro assays were used to analyse the phenotype and immune response activity in 92 patients with OSA (60 recently diagnosed untreated patients and 32 patients after 6 months of treatment with continuous positive airway pressure (CPAP)) and 29 healthy volunteers (HV). We determined that monocytes in patients with OSA exhibit an immunosuppressive phenotype, including surface expression of glycoprotein-A repetitions predominant protein (GARP) and transforming growth factor-β (TGF-β), in contrast to those from the HV and CPAP groups. High levels of TGF-β were detected in OSA sera. TGF-β release by GARP + monocytes impaired NK cytotoxicity and maturation. This altered phenotype correlated with the hypoxic severity clinical score (CT90). Reoxygenation eventually restored the altered phenotypes and cytotoxicity. This study demonstrates that GARP + monocytes from untreated patients with OSA have an NK-suppressing role through their release of TGF-β. Our findings show that monocyte plasticity immunomodulates NK activity in this pathology, suggesting a potential role in cancer incidence. Obstructive sleep apnoea induces reversible changes in the innate immune response; monocytes compromise NK cells http://ow.ly/q2yb309MRPt